P720 Is there a difference in trough levels and immunogenicity between Crohn's disease and ulcerative colitis patients treated with infliximab?. (16th January 2018) - Perdigoto, D; Macedo, C; Portela, F; Lopes, S; Ferreira, M; Ferreira, M; Mendes, S; Tomé, L
Abstract: Background: Immunogenicity directed to infliximab (IFX) administration can lead to secondary loss of response with the formation of anti-infliximab antibodies (AIA). Immunomodulators may play a role in reducing the immunogenicity in inflammatory bowel disease (IBD). We aimed to identify differences in immunogenicity directed to IFX between Crohn's disease (CD) and ulcerative colitis (UC). We also aimed to evaluate the role of immunomodulators - combined therapy (CT) in reducing the immunogenicity and clarify differences between both diseases. Methods: Single-centre retrospective cohort study based on patients with IBD treated with infliximab. Remission was defined as the absence of symptoms and C-reactive protein ≤ 0.5 mg/dl. Significant immunogenicity (SI) was considered as the simultaneous presence of IFX trough levels ≤ 1.0 µg/ml and AIA ≥ 10.0 ng/ml. Statistics done with SPSS (v. 20.0, IBM, Chicago, IL, USA), significance for p < 0.05. Results: A total of 116 patients were included. The most were female (56.8%), mean age of 39.4 ± 13.3 (18–74) years. The majority had CD (85 patients, 73.3%). Patients with indeterminate colitis were excluded. Patients were being treated with infliximab for at least 14 weeks after first administration; 59.5% patients were doing CT. Mean of 45.7 ± 35.5 months of follow-up. The median infliximab trough values for CD and UC were, respectively, 2.53 ± 2.32 and 2.35 ± 2.43 µg/ml. The presence of AIA was not significantly different in CD and UC, 23.5 vs. 41.9%, p = 0.052, respectively. However, the absolute AIA value was higher in UC (53.45 ± 83.87 ng/ml) than in CD (21.80 ± 55.61 ng/ml), p = 0.029. Regarding CD, 53 patients were doing CT, and from those, 17% developed AIA, compared with 34.4% from the 32 patients without CT, p = 0.067. In UC patients, from the 16 patients doing CT, 50% developed AIA compared with 33.3% of the 15 patients not doing CT, p = 0.347. There were 19 patients with SI (16.4% of total), 11 (12.9%) with CD and 8 (25.8%) with UC ( p = 0.098). Comparing the group with SI vs. without SI, the presence of SI was not connected to the absence of CT (47.4% vs. 52.6%, p = 0.308). In patients with CD, the presence of CT did not influence the development of SI (45.5% vs. 54.5%, p = 0.317); the same occurred for UC (50% vs. 50%, p = 1.0). Conclusions: The immunogenicity in UC patients seems higher, but it was not statistically different. The use of immunomodulators did not prove to reduce the formation of AIA significantly, especially in UC. Globally, combined therapy (IFX + immunomodulator) did not reduce the risk for SI, both in CD and UC.